GEOPOLITICS AND GEOPOETICS IN STANISŁAW KOLBUSZEWSKI’S BALTIC ESSAYS - Browarny, Wojciech; Zazula, Piotr (Via Latgalica, 2017)
The paper discusses Stanislaw Kolbuszewski’s essays devoted to the capitals of the Baltic States (W stolicach państw bałtyckich, Poznań 1939) that the author visited in the 1930s. Kolbuszewski’s aim was to familiarize the Polish reader with modern Lithuania, Latvia, and Estonia as seen through the eyes of a (friendly) stranger. The authors of the paper focus on the geopolitical and geopoetic ideas implicit in Kolbuszewski’s account of his travels to Riga, Tallinn and Kaunas, searching for the connections between geographic space, culture, civilization, history, traditions and the collective memory. What seems particularly intriguing about Kolbuszewski’s report is the dynamic interplay between the personal perspective of “the Other” and the numerous historical affinities between Poland and the Baltic states modifying that “otherness.”